Comparing perceived insecurity among customers and retail staff during service encounters. (July 2016) - Koistinen, Katri; Järvinen, Raija
Abstract: The study compares perceived insecurity by customers and retail staff during service encounters. The topic is important, because retailers invest millions of dollars in security. The framework of the study divides perceived insecurity into financial, physical, psychosocial and time-related insecurity. A total of 39 consumers participated in seven focus group discussions, and 34 retail staff members responded semi-structured interviews. The study confirms that from both customer and staff perspectives a high quality service encounter has an influence on perceived insecurity, and it diminishes disturbance and criminal activity. However, there are differences between customer and staff perspectives in many areas.